MetroMMC: electron-capture spectrometry with cryogenic calorimeters for science and technology - Ranitzsch, Philipp; Arnold, D.; Beyer, Jörn; Bockhorn, Lina; Bonaparte, J. J.; Enss, Christian; Kossert, Karsten; Kempf, Sebastian; Loidl, M.; Mariam, R.; Nähle, Ole Jens; Paulsen, Michael; et al. (Journal of low temperature physics, 2020)
Accurate decay data of radionuclides are necessary for many fields of science and technology, ranging from medicine and particle physics to metrology. However, data that are in use today are mostly based on measurements or theoretical calculation methods that are rather old. Recent measurements with cryogenic detectors and other methods show significant discrepancies to both older experimental data and theory in some cases. Moreover, the old results often suffer from large or underestimated uncertainties. This is in particular the case for electron-capture (EC) decays, where only a few selected radionuclides have ever been measured. To systematically address these shortcomings, the European metrology project MetroMMC aims at investigating six radionuclides decaying by EC. The nuclides are chosen to cover a wide range of atomic numbers Z, which results in a wide range of decay energies and includes different decay modes, such as pure EC or EC accompanied by $$γ $$γ- and/or $$β ^{+}$$β+-transitions. These will be measured using metallic magnetic calorimeters (MMCs), cryogenic energy-dispersive detectors with high-energy resolution, low-energy threshold and high, adjustable stopping power that are well suited for measurements of the total decay energy and X-ray spectrometry. Within the MetroMMC project, these detectors are used to obtain X-ray emission intensities of external sources as well as fractional EC probabilities of sources embedded in a $$4π $$4π absorber. Experimentally determined nuclear and atomic data will be compared to state-of-the-art theoretical calculations which will be further developed within the project. This contribution introduces the MetroMMC project and in particular its experimental approach. The challenges in EC spectrometry are to adapt the detectors and the source preparation to the different decay channels and the wide energy range involved, while keeping the good resolution and especially the low-energy threshold to measure the EC from outer shells.
P.C.-O. Ranitzsch, D. Arnold, J. Beyer, L. Bockhorn, J.J. Bonaparte, C. Enss, K. Kossert, S. Kempf, M. Loidl, R. Mariam, O.J. Nähle, M. Paulsen, M. Rodrigues, M. Wegner
Gesehen am 12.01.2021
Published online: 9 December 2019